Legal Regulation of Energy Safety in Ukraine and the European Union: Problems and Perspective - Shulga, Ievgenii; Kurylo, Volodymyr; Gyrenko, Inna; Savych, Serhii (European Journal of Sustainable Development, 2019)
Nowadays in Ukraine there is no single view on understanding of the strategy of development of energy safety, which profoundly and negatively affected the general state of national safety of the country. The purpose of the article is to analyze the current state of legal security of energy safety in Ukraine, check it for compliance with its obligations under the Association Agreement with the EU and other EU acts that proclaim the standards in the field of energy safety. This paper refers to the experience of the EU energy safety legislation. Furthemore, this study provides analysis of Ukrainian legislation in this field, draws attention to the existing conflicts and gaps, emphasizing the need to optimize legislation of Ukraine's energy safety according to the EU standards. Keywords: energy safety, energy law, the EU energy safety, energy safety of Ukraine, legislation of energy safety, adaptation of Ukrainian energy legislation to the EU standards.